2020
DOI: 10.1111/1467-8454.12178
|View full text |Cite
|
Sign up to set email alerts
|

Bitcoin—A hype or digital gold? Global evidence

Abstract: This study explores whether Bitcoin constitutes as a hedging instrument whilst seeking portfolio diversification opportunities among sustainable, conventional and Islamic asset classes since Bitcoin emerges as a distinct alternative investment and asset class across the world. We apply multivariate generalised autoregressive conditional heteroscedastic‐dynamic conditional correlation and continuous wavelet transforms based on the recent data set ranging from August 18, 2011, to September 10, 2018. First, our f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…Several studies have assessed the empirical nature of cryptocurrencies along with Islamic equity and capital markets to understand the riskreturn tradeoff and whether they provide diversification and hedging opportunities. For example, Uddin et al (2020) consider the role of bitcoins as hedging instruments in portfolio management. Using a comprehensive daily dataset of Islamic, convention, and sustainable assets, they reported that bitcoin values are mean-reverting in the long run, however, bitcoin provides portfolio diversification benefits to all equity markets both in the short and long run.…”
Section: Gjr-garch Methods Under Corrected DCC (Cdcc)mentioning
confidence: 99%
“…Several studies have assessed the empirical nature of cryptocurrencies along with Islamic equity and capital markets to understand the riskreturn tradeoff and whether they provide diversification and hedging opportunities. For example, Uddin et al (2020) consider the role of bitcoins as hedging instruments in portfolio management. Using a comprehensive daily dataset of Islamic, convention, and sustainable assets, they reported that bitcoin values are mean-reverting in the long run, however, bitcoin provides portfolio diversification benefits to all equity markets both in the short and long run.…”
Section: Gjr-garch Methods Under Corrected DCC (Cdcc)mentioning
confidence: 99%
“…Meng et al (2019) explored the impact of hedge fund fee diversification on portfolio returns and documented that such fee structure does not provide superior returns to investors. Ram (2019), 2020) and Uddin et al (2020) documented the evidence of higher risk-adjusted returns from investments in Bitcoin. Boal and Wiederhold (2021) stated that investments in commodities provided opportunities for better risk premia strategies and stated that long-only commodity investments provide diversification benefits and inflation protection.…”
Section: Diversification Benefits and Role Of Alternative Investments...mentioning
confidence: 99%
“…Satoshi Nakamoto made it "impossible" for the miners to solve the equation that can create new bitcoins after reaching this ceiling. This has led some to argue that bitcoin is "digital gold" (Uddin et al, 2020).…”
Section: Regulation Of Crypto-assets In the Eumentioning
confidence: 99%